Application of sumac and dried whey in female broiler feed - F. Kheiri; Y. Rahimian; J. Nasr (Archives Animal Breeding, 2015)
The present study aimed at investigating the effects of sumac and dried whey powder on growth performance, carcass traits, intestinal morphology, microbial population, and some biochemical parameters and antibody titer against Newcastle disease of female broiler chicks. A total of 360 1-day-old female broiler chicks with an average weight of 38 ± 0.42 g were randomly divided into three treatments. Each treatment was further divided into six replicates. Three treatments were used: chicks were fed by basal diet as control group, basal diet + 0.02% sumac powder (S), and basal diet + 0.02% dried whey powder (DW) for 42 days. Results showed that feed intake of chicks increased significantly in S and DW in comparison with the control group (P < 0.05). Body weight gain was also significantly higher in the treated groups. The serum concentration triglyceride and cholesterol of chicks decreased significantly by S and DW feeding. While low-density lipoprotein (LDL) level decreased significantly, high-density lipoprotein (HDL) levels increased in the S group. Antibody level increased titer against Newcastle disease significantly by feeding treated diet compared to the control group. Data from microbial population investigation showed that E. coli population decreased while Lactobacillus increased in S and DW groups. The data revealed an improvement in the body weight gain, feed conversion ratio because of increased intestinal morphology, antibody level, and some useful microbial population in female broiler chicks receiving the sumac and dried whey powder.